Self-Heat Recuperative Microwave and Hot-Air-Combined Drying of Lignite. Issue 6 (1st November 2016) - Zhao, Xiqiang; Wang, Wenlong; Mao, Yanpeng; Chen, Guifang; Jin, Chuanming; Yao, Liansheng; Song, Zhanlong
ABSTRACT: In this study, experiments on hot-air drying of lignite were conducted with some important parameters. The moisture content of lignite decreased from 33.40% to 20.84% when dried by hot air (temperature: 80°C, velocity: 4 m/s) alone for 30 min; the thermal efficiency of the hot-air dryer was about 82%. Later on, a self-heat recuperative microwave and hot-air-combined drying system for lignite was designed. The system was divided into three stages: The first stage was the preheat stage, using waste heat of steam evaporated in the microwave dryer to preheat the lignite; the second was the microwave drying stage, using microwaves to dry the preheated lignite; the third was the cooling stage, where dried lignite was cooled by the drying medium of the preheater. Assuming the final moisture content of dried product was 10.00%, the moisture content of lignite would reduce from 33.00% to 26.50% at the preheater and continue to reduce from 26.50% to 10.00% at the second stage. If half of the energy needed by the preheater was provided by the flue gas introduced, the moisture content of lignite would reduce from 33.00% to 21.55% at the preheater and continued to reduce from 21.55% to 10.00% at the microwave dryer.